Distinct degenerative phenotype of articular cartilage from knees with meniscus tear compared to knees with osteoarthritis. Issue 6 (June 2019) - Rai, M.F.; Tycksen, E.D.; Cai, L.; Yu, J.; Wright, R.W.; Brophy, R.H.
Summary: Objective: To compare the transcriptome of articular cartilage from knees with meniscus tears to knees with end-stage osteoarthritis (OA). Design: Articular cartilage was collected from the non-weight bearing medial intercondylar notch of knees undergoing arthroscopic partial meniscectomy (APM; N = 10, 49.7 ± 10.8 years, 50% females) for isolated medial meniscus tears and knees undergoing total knee arthroplasty (TKA; N = 10, 66.0 ± 7.6 years, 70% females) due to end-stage OA. Ribonucleic acid (RNA) preparation was subjected to SurePrint G3 human 8 × 60K RNA microarrays to probe differentially expressed transcripts followed by computational exploration of underlying biological processes. Real-time polymerase chain reaction amplification was performed on selected transcripts to validate microarray data. Results: We observed that 81 transcripts were significantly differentially expressed (45 elevated, 36 repressed) between APM and TKA samples (≥ 2 fold) at a false discovery rate of ≤ 0.05. Among these, CFD, CSN1S1, TSPAN11, CSF1R and CD14 were elevated in the TKA group, while CHI3L2, HILPDA, COL3A1, COL27A1 and FGF2 were highly expressed in APM group. A few long intergenic non-coding RNAs (lincRNAs), small nuclear RNAs (snoRNAs) and antisense RNAs were also differentially expressed between the two groups. Transcripts up-regulated in TKA cartilage were enriched for protein localization and activation, chemical stimulus, immune response, and toll-like receptor signaling pathway. Transcripts up-regulated in APM cartilage were enriched for mesenchymal cell apoptosis, epithelial morphogenesis, canonical glycolysis, extracellular matrix organization, cartilage development, and glucose catabolic process. Conclusions: This study suggests that APM and TKA cartilage express distinct sets of OA transcripts. The gene profile in cartilage from TKA knees represents an end-stage OA whereas in APM knees it is clearly earlier in the degenerative process.